Traditional Retail Decision-Making and Coordination Considering Online Reviews and Offline Services - Chen, Dong; Liu, Yong; Ren, Wen-wen (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
This study investigates optimal decision-making in a manufacturer-led dual-channel supply chain, focusing on the significant influences of online reviews and offline services on consumer behavior. We develop Stackelberg game models to analyze the impacts of online review investment, service spillover effects, and cross-price sensitivity under both decentralized and centralized decision-making structures. To coordinate the supply chain, we design a two-part pricing contract. Our findings reveal that increased investment in online reviews leads to a higher online direct price for the manufacturer and a greater offline service level from the retailer, while the retailer’s offline retail price decreases. Furthermore, a higher service spillover effect coefficient results in increased offline service levels, online prices, and offline prices. The analysis confirms that supply chain profits under centralized decision-making exceed those under decentralized decision-making. The proposed two-part pricing contract effectively achieves supply chain coordination and improves overall performance.